Applying the framework to study climate-induced extremes on food, energy, and water systems (C-FEWS): The role of engineered and natural infrastructures, technology, and environmental management in the United States Northeast and Midwest - Vörösmarty, Charles J.; Melillo, Jerry M.; Wuebbles, Donald J.; Jain, Atul K.; Ando, Amy W.; Chen, Mengye; Tuler, Seth; Smith, Richard; Kicklighter, David; Corsi, Fabio; Fekete, Balazs; Miara, Ariel; et al. (Frontiers in Environmental Science, 2023)
Change to global climate, including both its progressive character and episodic extremes, constitute a critical societal challenge. We apply here a framework to analyze Climate-induced Extremes on the Food, Energy, Water System Nexus (C-FEWS), with particular emphasis on the roles and sensitivities of traditionally engineered (TEI) and nature-based (NBI) infrastructures. The rationale and technical specifications for C-FEWS component models and supporting data sets are detailed in an accompanying paper (Vörösmarty et al., this issue). We report here on initial results applying this framework in two important macro-regions of the United States (Northeast, NE; Midwest MW), where major decisions affecting global food production, biofuels, energy security and pollution abatement require critical scientific support. We present the essential FEWS-related hypotheses that organize our work with an overview of the methodologies and experimental designs applied. We report on initial C-FEWS framework results using five emblematic studies that highlight how various combinations of climate sensitivities, TEI-NBI deployments, technology, and environmental management determine regional FEWS performance. Despite their relative simplicity, these initial experiments yield important insights. We find FEWS performance impacted by climate stress, but the sensitivity is strongly modified by technology choices applied to both ecosystems (e.g., cropland production using new cultivars) and engineered systems (e.g., thermoelectricity from different fuels and cooling types). We tabulate strong legacy effects stemming from decisions on managing NBI (e.g., multi-decade land conversions that limit long-term carbon sequestration). The framework also enables us to reveal how broad-scale policies aimed at a particular net benefit can result in unintended and potentially negative consequences. For example, tradeoff experiments identify the regional importance of TEI in the form wastewater treatment and NBI via aquatic self-purification, guiding potential investments point and/or non-point source water pollution control. Another example uses a reduced complexity model to demonstrate a FEWS tradeoff in the context of water supply, electricity production, and thermal pollution. Such results demonstrate the importance of TEI and NBI in jointly determining FEWS performance, their vulnerabilities, and their resilience to extreme climate events. These infrastructures constitute the “policy levers” which can actively be engaged to mitigate the challenge of contemporary and future climate change.